The impact of micro-mineral sources and their availability on hepatic lipid metabolism in Atlantic salmon (Salmo salar) - Hundal, Bjørg Kristine (The University of Bergen, 2018)
The increased use of plant-based ingredients in aquafeeds for Atlantic salmon has led to an increase in phytate, an antinutrient binding micro minerals and reducing their bioavailability. It has been suggested that the chemical form of the minerals (organic/inorganic) can alter their bioavailability, especially in feeds with high phytate content. The functional role of minerals in hepatic intermediary metabolism is poorly understood in fish, though studies have shown that dietary mineral levels can affect hepatic lipid metabolism. However, this effect has not been examined in the nutritionally relevant context of dietary mineral availability in plant ingredient based diets. The aim of this study was to investigate whether availability and chemical form of zinc, selenium and manganese affected liver lipid metabolism of Atlantic salmon. A feeding trial involving five different diets was performed. The two control diets contained inorganic Zn, Se and Mn with different phytate contents. Unfortunately, the difference in phytate turned out to be too small to have any effect on the mineral digestibility. The three other diets all had the higher phytate content and in each diet one of the inorganic minerals Zn, Se and Mn were exchanged with chelate of Zn, selenium methionine or chelate of Mn, respectively. The mineral content of the liver was investigated to see if there had been any changes to the mineral status. No significant differences were found. Genes involved in β-oxidation (PPARα, CPT1), lipogenesis (LXR, SREBP1, FAS), bioconversion into LC-PUFA (Δ5Fad, Δ6Fad) and transport out of the liver (ApoB100) were examined to see if there were any effects on hepatic lipid metabolism. There were no significant effects on LXR, FAS, PPARα, CPT1, Δ5Fad or Δ6Fad. ApoB100 and SREBP1 were significantly reduced in the higher phytate control group compared to the lower phytate control. However, these two groups had the same chemical form of all the minerals, no impact of phytate on mineral digestibility was detected and there ...